2012
DOI: 10.3109/13880209.2012.679985
|View full text |Cite
|
Sign up to set email alerts
|

Blood glucose lowering property of water in oral insulin-fed diabetic rats

Abstract: Insulin-water interaction could be one reason where water migration from the gastrointestinal lumen into systemic circulation is reduced and blood glucose lowering capacity of deionized water is negated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Nevertheless, the Tween 80 decorated nanoparticles exhibited a remarkably low blood glucose lowering effect when compared to the Tween 80‐free nanoparticles (Figure ). Previous research indicated that deionized water exerted blood glucose lowering effect via dilution of systemic circulation by absorbed water as reflected by the reduction in concentration of marker red blood cells and glucose itself [2]. The migration of water from gastrointestinal lumen to systemic circulation can be affected by drug/excipient‐water interaction thereby reducing the blood glucose lowering capacity of deionized water.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, the Tween 80 decorated nanoparticles exhibited a remarkably low blood glucose lowering effect when compared to the Tween 80‐free nanoparticles (Figure ). Previous research indicated that deionized water exerted blood glucose lowering effect via dilution of systemic circulation by absorbed water as reflected by the reduction in concentration of marker red blood cells and glucose itself [2]. The migration of water from gastrointestinal lumen to systemic circulation can be affected by drug/excipient‐water interaction thereby reducing the blood glucose lowering capacity of deionized water.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental diabetes was induced in rats according to a modified protocol using streptozotocin solution prepared in 0.1 m citrate buffer pH 4.5 and sterilized by filtration through 0.22 μ m MILLEX GP Syringe Driven Filter Unit (Millipore Corporation) [2]. Following 15 h of fasting, each rat was administered with a single intraperitoneal injection of the freshly prepared streptozotocin solution at the dose of 55 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations